2015
DOI: 10.1177/1350650115594406
|View full text |Cite
|
Sign up to set email alerts
|

Study of acoustic performance of textured journal bearing

Abstract: The acoustic performance of a textured journal bearing is studied based on computation fluid dynamic (CFD) theory and acoustic equation involved. First, a micro-grooved journal bearing is modeled through commercial software ANSYS. Then, the acoustic power levels for the journal bearing at different depths, widths, and positions of the dimples are solved through the CFD method. The numerical results show that the existence of dimples can lower the acoustic power level of the bearing. Moreover, this reduction de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Their finding was also confirmed by Ji et al [4]. Later, Meng and his group [5][6][7] studied more deeply the effect of compound groove texture in various forms on tribological and acoustic performance through the computational fluid dynamics (CFD) method. Their main results stated that the optimal dimple compound can reduce noise levels and increase load-carrying capacity and frictional forces.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Their finding was also confirmed by Ji et al [4]. Later, Meng and his group [5][6][7] studied more deeply the effect of compound groove texture in various forms on tribological and acoustic performance through the computational fluid dynamics (CFD) method. Their main results stated that the optimal dimple compound can reduce noise levels and increase load-carrying capacity and frictional forces.…”
Section: Introductionmentioning
confidence: 67%
“…The basic geometry of the journal bearing used here adopts the geometry as presented by Meng, et al [6]. In this study, the concept of the heterogeneous rough/smooth bearing is introduced in which the rough condition is applied on certain areas while the others are smooth.…”
Section: Modelmentioning
confidence: 99%
“…Later, Bouaziz et al [25] observed that the sound pressure is markedly influenced by the angular velocity of the journal. In many works of recent literature, Meng et al [26][27][28][29] presented a deep investigation of the acoustic performance of journal bearing in addition to the tribological performance dealing with the positive effect of the compound texture. Their main finding revealed that the well-chosen compound dimple (i.e., its depth, width, and position in the optimal pattern) can reduce the bearing noise and improve the load support compared to the smooth bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it has been proven that surface texturing shows a good behavior in improving the load-carrying capacity, stiffness, and reducing the friction and the noise of bearings at some circumstances. 14 Hamilton et al. 5 firstly pointed out that there exists a hydrodynamic pressure lifting in micro-asperities of a textured surface.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it has been proven that surface texturing shows a good behavior in improving the load-carrying capacity, stiffness, and reducing the friction and the noise of bearings at some circumstances. [1][2][3][4] Hamilton et al 5 firstly pointed out that there exists a hydrodynamic pressure lifting in micro-asperities of a textured surface. Then, since Etsion et al [6][7][8] successfully applied surface texturing to mechanical seals, researchers started to pay intensive attentions to this new technology.…”
Section: Introductionmentioning
confidence: 99%